PELATIHAN KOMPUTER UNTUK MENINGKATKAN KETERAMPILAN WARGA BELAJAR - Aulia, Lidiana; Khoiruumah, Ilma; Anggriani, Mita; Yuliani, Lulu (Jurnal Empowerment, 2025)
This research was conducted to try to answer problems related to the implementation of non-formal education programs, especially in computer training programs to increase the knowledge and skills of learning citizens. Through this research it is hoped that it can provide input for non-formal education program organizers in finding alternatives that can empower the community. the location of the research was carried out at PKBM Cerdik, Tamansari. The results of the evaluation of the implementation of the training program show that computer training at the Smart PKBM has been able to increase the knowledge and skills of learning residents in the field of computers, so that they can play a role in keeping pace with technological developments. However, in the implementation of the training, several obstacles were found which became materials for improvement for the next implementation, including the lack of personnel in the field of computer technicians, limited training funds, and low motivation among learning residents to attend training.